Edukasi Keperawatan sebagai Strategi Pencegahan dan Pengendalian Penyakit Kronis di Masyarakat Batam - Nasution, Nurhafizah; Dasaryandi, Kiki Rizki (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2025)
Chronic diseases such as hypertension, diabetes mellitus, heart disease, and chronic obstructive pulmonary disease (COPD) are a growing health problem in Batam City. Lack of public awareness regarding early detection, unhealthy lifestyles, and limited access to health information are major risk factors. This community service activity aims to provide nursing education as a promotive and preventive strategy for preventing and controlling chronic diseases. The methods used included health education, demonstrations of healthy lifestyle practices, and basic health examinations (blood pressure, blood sugar, and body mass index). The results of the activity showed an increase in participants' knowledge regarding risk factors for chronic diseases and strategies for controlling them. Nursing education has proven effective in increasing public awareness in Batam to adopt healthy lifestyle behaviors.